Money Politics and Political Corruption in Indonesia: A Structured Literature Review and the Electoral Corruption Cycle Framework - Kevin Jeremia Pakpahan (Lembaga Kajian Sosial Politik Aceh (LaKaspia), 2026)
Money politics and political corruption are interconnected problems in Indonesia’s electoral democracy. However, existing studies often examine electoral mobilization and post-election abuses of power separately, leaving the relationship between these phenomena insufficiently integrated. This study aims to: (1) synthesize findings on the relationship between money politics and political corruption in Indonesia; (2) identify the institutional and political factors that enable this relationship to recur; and (3) develop a conceptual framework for the Electoral Corruption Cycle. The study employed a structured literature review informed by systematic review principles and guided by the transparency principles of PRISMA 2020. Nine journal articles published between 2018 and 2025 and available as of December 30, 2025, were included in the thematic synthesis. The analysis generated five themes: structural drivers of political corruption, money politics and electoral mobilization, post-election abuses of power, impacts on democratic quality, and prevention strategies. The findings indicate that high electoral costs, a lack of transparency in political financing, patronage relations, weak oversight, and limited law enforcement may create a risk pathway linking material-based electoral mobilization to the misuse of public authority. This relationship is conditional rather than automatic and is shaped by funding sources, dependence on donors, party organization, and institutional accountability. The study proposes the Electoral Corruption Cycle as an integrative conceptual framework consisting of four phases: political capital accumulation, material distribution, resource recovery and the fulfillment of political obligations, and cycle reproduction. This framework provides an exploratory model for examining the connections among pre-electoral, electoral, post-electoral, and subsequent electoral phases.